RESPON PERTUMBUHAN DAN HASIL TANAMAN SELADA (LACTUCA SATIVA L.) PADA BERBAGAI JENIS MEDIA TANAM - Alsifa, Yuli; Darnetti, Darnetti; Nofrianil, Nofrianil; Rahmadani, Fathiah (Institute of Computer Science (IOCS), 2025)
Lettuce (Lactuca sativa L.) is a horticultural commodity that is widely consumed and has a continuously increasing market prospect, but production in Lima Puluh Kota Regency has not developed optimally. This research was conducted in the practice field of the Payakumbuh State Agricultural Polytechnic, West Sumatra in March-May 2024. The purpose of this study was to analyze the effect of various types of planting media on the growth and yield of lettuce (Lactuca sativa L.) plants. The study used a one-factor Randomized Block Design (RBD) with four treatments, namely P1 (soil + 100% NPK), P2 (soil + rice husk charcoal + chicken manure + 50% NPK), P3 (soil + rice husk charcoal + cow manure + 50% NPK), and P4 (soil + rice husk charcoal + goat manure + 50% NPK) with six replications. Observed parameters included plant height, number of leaves, stem diameter, root weight, plant fresh weight, and shoot-root ratio. Data analysis used ANOVA followed by Duncan's test (DMRT) at the 5% level. The results showed that the growing medium significantly affected all observed parameters, including plant height, stem diameter, number of leaves, root weight, and plant fresh weight. The best treatment was obtained with soil + rice husk charcoal + goat manure (1:1:1) + 50% NPK, which resulted in the highest growth and production of lettuce. This combination of organic and inorganic materials has been proven to increase the fertility of the growing medium and the efficiency of chemical fertilizer use. This study shows that the balanced use of manure and rice husk charcoal has the potential to support sustainable lettuce cultivation, although further testing in field conditions and with different varieties is still needed.